Enhanced dielectric properties of poly (vinylidene fluoride) composites filled with polystyrene 2% divinyl benzene modified graphite nanopowders. (23rd February 2020) - Moharana, Srikanta; Mishra, Mukesh K.; Dash, B.; Mahaling, R. N.
ABSTRACT: Graphite nanopowder/poly (vinylidene fluoride) (GNP-PVDF) composite films were prepared by using polystyrene 2% divinyl benzene (PDB) via a solution casting technique. The composites had a higher dielectric constant (≈ 76) and relatively lower dielectric loss (<1), than that of the composite GNP-PVDF and pristine PVDF at 1000 Hz. The AC electrical conductivity spectrum well obeyed Jonscher's universal power law. The investigation of the polarisation–electric field loop showed a higher remnant polarisation (3. 15 μC/cm 2 ), when compared with PVDF. It is believed that the PDB-modified GNP-PVDF composites would be a promising material for electronic applications.